ANALISIS IMPLEMENTASI STRATEGI RELATIONSHIP MARKETING PADA PERUSAHAAN PDAM WAY RILAU BANDAR LAMPUNG - Reza gama prasadana; K Bagus Wardhianto (Jurnal Kompetitif Bisnis, 2022)
Relationship Marketing is a business model with the aim of identifying, anticipating, understanding customer needs by applying the dimensions of trust, commitment, communication, and conflict handle. At PDAM Way Rilau Bandar Lampung, the purpose of this study is to determine the form of a marketing relationship strategy and to find out how effective this strategy is in dealing with existing complaints. There were 6 informants in this study, this research is a descriptive study with a qualitative approach. The results of the study show that trust, commitment, communication, and conflict handle have been well developed with a fairly even distribution of information. However, even though the strategy provided by PDAM is good, the strategy This cannot be said to be successful because the treatment given by the company has not been evenly distributed, there are still consumers who feel unsatisfied with the services provided, even so the company is trying its best to help it by moving consumer water installations to better dam sources so that all consumers Those who have not felt that they have received a good quality product will feel it as well as other consumers.